(untitled) (CIPEEX, 2022)
IT IS NOTORIOUS THAT OVER TIME THE ENVIRONMENT HAS BEEN DEGRADING MORE AND MORE WITH EACH PASSING YEAR. THE GREAT RESPONSIBLE FOR THIS IS THE HUMAN BEING, WHO WITH HIS GREAT THIRST FOR DOMINATING NATURE AND GETTING MORE AND MORE POWER, HAS BEEN CARRYING A GREAT MASS OF DESTRUCTION, CAUSING NATURAL DISASTERS THAT DEGRADE THE PLANET LITTLE BY LITTLE, LIKE THE GLOBAL WARMING. WITH THIS IN MIND, NATUVATION WAS PLANNED, AN ATTEMPT TO MAKE PEOPLE AWARE OF THEIR OWN ACTIONS. THIS WORK AIMS AT THE STUDY AND PRACTICAL DEMONSTRATION THROUGH THE DEVELOPMENT OF A WEBSITE IN WHICH THE USER IS INFORMED ABOUT THE CURRENT CONDITIONS OF THE ENVIRONMENT, IN AN INTERACTIVE AND DESCRIPTIVE WAY, MAKING IT POSSIBLE TO RAISE HIS AWARENESS. BESIDES CONNECTING THEM WITH NGOS THAT HAVE THE SAME OBJECTIVE. FOR ITS CONCEPTION, IT WAS USED THE KNOWLEDGE ACQUIRED THROUGH THE LEAN INCEPTION METHODOLOGY, DEVELOPED BY PAULO CAROLI, ALONG WITH THE KNOWLEDGE ACQUIRED IN THE DISCIPLINES OF THE SOFTWARE ENGINEERING COURSE. TO ARCHITECT THE DEVELOPMENT PROCESS, THE SCRUM FRAMEWORK WAS USED ALONG WITH KANBAN, IN THIS WAY THE FUNCTIONALITIES AND THE SPRINTS PROCESS WERE ASSIGNED. A STUDY ON UI AND UX WAS STARTED, SO THAT THE SOFTWARE COULD BE USED WITH GREATER MASTERY. THROUGH THIS PROJECT, IT SEEKS TO RAISE PEOPLE’S AWARENESS TO ENCOURAGE THEM TO CREATE A HABIT OF LIFE, AND THUS AFFECT THEM AND THE ENVIRONMENT IN A POSITIVE WAY, CONTRIBUTING TO A BETTER WORLD FOR ALL.